(untitled) (Brazilian Journal of Radiation Sciences, 2021)
Granitic rocks, widely used as building materials, are known to contain natural radionuclides and can be an important source of radiation for the population. Thirty-four samples of granite rocks from geological occurrences in Paraná state were measured with an HPGe detector for evaluation of226Ra, 232Th and 40K activity concentrations. The effective annual external dose was evaluated from these radionuclides activities using a dosimetric room model with dimensions 4 m x 5 m x 2.8 m in which all wallsare internally coated with granites of thickness 2 cm and considering an annual exposure time of 7000 h. This value was suggested by the European Commission on Radiological Protection for superficial coating materials. The internal exposure was evaluated from radon air concentration of the model room, simulated from an exhalation rate of 222Rn, determined with CR-39 solid state nuclear track detectors using the sealed can technique, considering a ventilation rate of 0.5 h-1 and an annual exposure time of 7000 h. The results of this study showed that the increase in the annual effective dose ranged from 62 ± 3 μSv.a-1 to 138 ± 1 μSv.a-1 from external gamma rays and the increase in the annual effective dose ranged from 0.39 ± 0.04 μSv.a-1 to 70 ± 4 μSv.a-1 from radon inhalation. All results stayed below 1 mSv.a-1 recommended by the European Commission on Radiological Protection.